A homozygous frame‐shift variant in PROSER1 is associated with developmental delay, hypotonia, genitourinary malformations, and distinctive facial features. Issue 5 (13th March 2022) - Salah, Azza; Almannai, Mohammed; Al Ojaimi, Mode; Radefeldt, Mandy; Gulati, Nishtha; Iqbal, Maria; Alawbathani, Salem; Al‐Ali, Ruslan; Beetz, Christian; El‐Hattab, Ayman W.
Abstract: We report four children from three related families who presented with a similar phenotype characterized by developmental delay, hypotonia, seizures, failure‐to‐thrive, strabismus, drooling, recurrent otitis media, hearing impairment, and genitourinary malformations. They also shared common facial features including arched eyebrows, prominent eyes, broad nasal bridge, low‐hanging columella, open mouth, thick lower lip, protruding tongue, large low‐set ears, and parietal bossing. Exome sequencing for affected individuals revealed a homozygous frame‐shift variant, c.1833del; p.(Thr612Glnfs*22), in PROSER1 which encodes the proline and serine rich protein 1 (PROSER1). PROSER1 has recently been found to be part of the histone methyltransferases KMT2C/KMT2D complexes. PROSER1 stabilizes TET2, a member of the TET family of DNA demethylases which is involved in recruiting the enhancer‐associated KMT2C/KMT2D complexes and mediating DNA demethylation, activating gene expression. Therefore, PROSER1 may play vital and potentially general roles in gene regulation, consistent with the wide phenotypic spectrum observed in the individuals presented here. The consistent phenotype, the loss‐of‐function predicted from the frame‐shift, the co‐segregation of the phenotype in our large pedigree, the vital role of PROSER1 in gene regulation, and the association of related genes with neurodevelopmental disorders argue for the loss of PROSER1 to be the cause for a novel recognizable syndrome. Abstract :